eDNA confirms lower trophic interactions help to modulate population outbreaks of the notorious crown-of-thorns sea star - Kennedy Wolfe; Amelia A. Desbiens; Frances Patel; Sarah Kwong; Eric Fisher; Peter J. Mumby; Sven Uthicke (Proceedings of the National Academy of Sciences, 2025)
Variability in predator–prey interactions can modulate population dynamics with impacts scalable to entire ecosystems. As notorious corallivores, crown-of-thorns sea stars (CoTS; Acanthaster spp.) have caused extensive losses of coral habitat during unexplained population outbreaks across the Indo-Pacific. While predation of adult CoTS may help to suppress their outbreaks, it does not sufficiently explain their profound boom-bust dynamics and so remains equivocal. Factors influencing early postsettlement mortality are generally more impactful on population size, thus lower trophic interactions involving juvenile CoTS may better contribute to outbreak prevention. We evaluated the impact of key predatory decapods that interact with juvenile CoTS in their coral rubble nursery before they emerge as destructive corallivores. Decapod density was influenced by habitat complexity and varied regionally, inverse to spatial trends in CoTS outbreaks on the Great Barrier Reef. Using eDNA gut content analysis, we confirmed seven species (~12% of individuals) of wild-caught decapod, collected from two reefs separated by >1,000 km, as CoTS predators. Owing to spatial variation in predator abundance and community structure, we estimated potential (previous aquarium experiments) and realized (eDNA results here) rates of CoTS consumption were ~3-fold and ~1.6-fold lower, respectively, in outbreak hotspots. Through combination of field and molecular techniques, we demonstrated the appreciable impact of cryptic predators on early population success of this nuisance species, which expands our knowledge of CoTS outbreaks, pest species management, and reef conservation. Resolving predator–prey interactions at lower levels of the ecosystem can be crucial to understanding broader ecological outcomes.